Piano trio in G major, op. 1, no. 2, Clementi edition - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Clementi & Co.; United Kingdom; London, 2023)
Early edition of the parts of the Piano trio in G major, op. 1, no. 2, published by Clementi.